Autobiografia: história da minha formação acadêmica - SANTOS, Valquíria da Silva dos (2021)
This one Job of Course Completion - TCC is an Autobiography: History of My Academic Formation. The Autobiography is a descriptive work that recounts not only the trajectory of my scholastic formation, but also a synthesis of some of the most striking family moments and my academic background. Being of poor family and children of farmers, I had good and bad moments in the city of New Brazil, where the memories are eternal. In this Autobiography, I intend to describe my life trajectory as a pupil of the infantile education until the academic inclusion. Aiming to describe the first contact with personal and professional experiences acquired in the course of my life. It is extremely important to remember the phases of our life both in childhood and adulthood and remember the professional achievements. The methodology of work presents a bibliographical research that deals with theoretical foundation to the trajectory of my life. The main objective is to value the growth of a student, because it is worth remembering that many years of experience in a school space and that many people do not have that moment to remember and make an analysis of what they experienced until arriving at a conclusion of I appreciate this moment to say that it is of great significance to be able to remember and experience the second time my life and today I affirm to be prepared for the market of the work with higher education in education field.